Sensitivity versus polarisation in multilayer optical thin film design - Efrem Ejigu; Beartys Lacquet (South African Journal of Science)
The design of a polarised optical filter is more complicated than that of a filter where the polarisation effect does not exist (at a normal angle of incidence). An error in the optical parameters, such as the physical thickness or refractive index of a layer, results in a change in the spectral performance of the multilayer structure. The correlation between error sensitivity and the polarisation effect of light in structures designed at an oblique angle was investigated. To illustrate the correlation, a perpendicular (S) and parallel (P) polarised beam splitter, at 0.9818 Âµm central wavelength, designed by genetic algorithm, was used. The beam splitter changes its state of polarisation according to the error in thickness simultaneously induced in each of the layers. The error was calculated by optimising the original design. The observation of the change of the state of polarisation as a result of error sensitivity leads to a different method of designing pure S-polarised or P-polarised optical filters.